PAYROLL ADMINISTRATION SYSTEM AT PT. SOLID UTAMA NUSANTARA BY USING MICROSOFT VISUAL FOXPRO 9.0 - Juliana Dwijanti Diah PSL; Melani Dewi Lusita, SKom, MMSI (Jurnal Sistem Informasi, 2007)
The increasing administrative activities at PT. Main Solid Archipelago and thegrowing need for a wide range of information about personnel, especially the writertrying to help create a system of personnel administration at this company. In apayroll system that has not used the application must be very difficult when to seekemployee data or files related to personnel and payroll. This will make the systemslow, errors caused by wrong at the time input and for different data transfer with theinput. By using the proposed payroll applications, particularly for employee datacollection, data entry is expected to be in accordance with the expected output, so thatthe mistakes that usually occur can be suppressed to a minimum and the process wasmuch faster.With the new computerized system, expected flow of information can move faster sothat the efficiency and effectiveness of the work can be achieved to the maximumextent possible.